Dressler's syndrome after right ventricular infarction. - Streifler, J. (BMJ Group, 1984)
Undiagnosed myocardial infarction of the right ventricle presented as Dressler's syndrome. Radioisotopic diagnostic procedures including first-pass and multigated acquisition nuclear angiography ( MUGA ) and thallium-201 perfusion studies enabled a retroactive diagnosis of myocardial infarction, showed it to be in the right ventricle, and clarified the aetiology of the unexplained fever and pleuropericarditis.